Anti-stress properties of buprenorphine: a better choice for stress-induced relapse to drug addiction - Ahmad Bidin, Mohammad Ashraf; Rosman, Nurul Nazierah; Suhaimi, Maryam Saadah; Syd Mohmad Faudzi, Syed Mohd Syahmi; Ridzwan, Irna Elina (2015)
Compared to methadone, buprenorphine has a unique pharmacological profile in which it is a partial agonist at the mu- and NOP, but antagonist at the kappa-opioid receptors. This gives advantage to buprenorphine to have lesser abusive tendency and has ability to reduce relapse to drug taking. Previous studies had shown that stress, which has been linked to relapse, increased the release of dynorphin (an endogenous kappa-opioid receptor agonist) and potentiates the rewarding effects of morphine. In this study, we tested if buprenorphine treatment has ability to block the drug seeking behaviour in mice using a conditioned place preference (CPP) paradigm. Initially, a modified forced-swim test (FST) was conducted for two consecutive days to induce stress by testing for immobility in mice. A significant difference between control and treatment groups (n = 8 for each group, P < 0.05) was observed on day 2 of FST trial which indicates the ability of buprenorphine (0.3 mg/kg) to reduce stress. Following FST, the mice were conditioned in two different compartments using biased method. The time spent in each compartment was calculated. It was found that there was no significant difference (P > 0.05) in the time spent for the treatment group (n = 8) during post morphine-conditioning session compared to their baseline, which suggested that buprenorphine has the ability to prevent morphine-seeking behaviour as compared to the control group (n = 8, P < 0.05) . These results suggest the advantage of buprenorphine as therapeutic agent to treat stress-induced relapse in drug addiction.